The Impact of Digital Transformation on Enterprise Performance - Luo, Xiaoyu; Chaiprasit, Kanokporn (Rajapark Journal, 2024)
This study aims to explore the impact of digital transformation on enterprise performance. The samples came from manufacturing enterprises in China to explore the relationship between digital transformation and enterprise performance. This paper uses a sample of 400, which is more than 5 times the number of observed variables, which is 280. This study uses quantitative analysis methods to test the research hypotheses of this study. It adopts the structural equation modeling (SEM) method to verify the effectiveness of the proposed theoretical framework. A questionnaire was also used to collect data. This study collected 400 first-hand pieces of information in the form of questionnaires and used AMOS and SPSS statistical software to process and analyze the data. The empirical analysis of this study confirms that digital transformation has a positive impact on enterprise performance, which not only provides a new perspective for theoretical research but also provides practical suggestions for companies to achieve sustainable competitive advantages in the digital era.